2022
DOI: 10.3389/fagro.2022.941111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approaches for improving resistance to Phytophthora crown rot caused by P. cactorum in strawberry (Fragaria × ananassa)

Abstract: Phytophthora crown rot (PhCR) caused by Phytophthora cactorum is one of the most damaging soilborne diseases of strawberry in the United States and worldwide. Limitations on fumigants such as methyl bromide have led to deterioration in the control of P. cactorum in recent years. The development of resistant varieties is a critical component of the strategy for combatting this soilborne disease. Here, we review the biology of the pathogen, molecular mechanisms of infection, and management of PhCR in strawberry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…The strawberry defence system against pathogens, including P. cactorum , has been extensively reviewed and is similar to the defence systems of other plants [ 37 , 38 ]. In the last two decades, several studies have identified the genetic resources of resistance to P. cactorum in different strawberry accessions and genotypes [ 19 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strawberry defence system against pathogens, including P. cactorum , has been extensively reviewed and is similar to the defence systems of other plants [ 37 , 38 ]. In the last two decades, several studies have identified the genetic resources of resistance to P. cactorum in different strawberry accessions and genotypes [ 19 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from Jiménez et al ( 2023 ) highlighted the benefits of incorporating underutilized gene bank diversity and genomic prediction in breeding to enhance resistance to P. cactorum by enabling the discovery of individuals carrying advantageous alleles that are either rare in the population or not present in modern cultivars. A recent review by Sharma et al ( 2022 ) explored the genomic approaches to improving resistance to P. cactorum in cultivated strawberry and highlighted the potential use of CRISPR gene editing in cultivated strawberry.…”
Section: Integrated Disease Management Strategiesmentioning
confidence: 99%
“…In the studies carried out, Phytophthora was initially determined only from soil or crown could. But as a result of the studies carried out in subsequent processes, it was determined that isolates obtained from other host plants and strawberry fruit also caused leather rot [43,44]. Phytophthora cactorum was first recorded as ground leather rot on fruits and crown rot in strawberries [44].…”
Section: Soil-borne Diseases In Strawberrymentioning
confidence: 99%
“…But as a result of the studies carried out in subsequent processes, it was determined that isolates obtained from other host plants and strawberry fruit also caused leather rot [43,44]. Phytophthora cactorum was first recorded as ground leather rot on fruits and crown rot in strawberries [44]. Owing to the continual presence of strawberry plants in the cultivation of perennials and plantations, the source of inoculum might include oospores [45].…”
Section: Soil-borne Diseases In Strawberrymentioning
confidence: 99%